An Application of the Discovery Earning Model to Analyze Class V Fiction and Nonfiction Stories - Rozi, Ahmas Souma Fahrur; Mahmudah, Masrurotul; Aisyah, Nurul (International Journal on Advanced Science, Education, and Religion, 2025)
This research aims to determine the application of the Discovery Learning learning model in improving the ability to analyze fiction and non-fiction stories in class V students at SDN 3 Bumi Nabung Baru. The approach used in this research is descriptive qualitative research. The research subjects used were class V teachers and class V students with a total of 14 students. The method used in collecting data was observation, interviews and documentation. The focus of this research is the application of discovery learning to determine students' analytical skills in fiction and non-fiction stories. The success of student analysis in stories can be determined from the indicators that have been determined. The results of the research show that there is an increase in students' analytical skills in the learning process by applying the discovery learning learning model